Gambaran Gejala Computer Vision Syndrome Pada Mahasiswa Fakultas Kedokteran Universitas HKBP Nommensen MedanTahun 2019/2020 - Halawa, Evan Marteen; Zaluchu, Ristarin Paskarina; Jirwanto, Hendra (Universitas HKBP Nommensen, 2022)
Background: The use of computers among students is now a necessary, especially for medical students both study and entertainment. This situation can increase the risk of Computer Vision Syndrome (CVS). Computer Vision Syndrome (CVS) is a bunch of symptoms on eye and vision-related problems by prolonged use of computers (such as tablets, e-readers, smartphones, etc.). Objective: This study aimed to find out the representation of CVS symptoms experienced by medical students in Medical Faculty of Universitas HKBP Nommensen Medan. Methods: This study is an observational descriptive with cross sectional design. The subjects were 270 students of Medical Faculty Universitas HKBP Nommensen Medan, was elected by total sampling technique due to inclusion and exclusion criteria. The instrument of this study was a questionnaire consist of 30 questions. Results: The results showed that the most common symptoms of CVS experienced by students on Medical Faculty of Universitas HKBP Nommensen were sensitivity to light as many as 219 people (81.1%), neck and back pain as many as 214 people (79.3%) and eye strain as many as 210 people (77.8%). The maximum duration of computer use by students of Medical Faculty of Universitas HKBP Nommensen Medan is >4 hours (90.4%). Conclusion: In this study was found that the most experienced symptom of CVS was light sensitivity. Based on the severity, CVS mild symptoms experienced are dry eye and irritation, moderate on eye strain, and severe on light sensitivity.